HiSpots®: A novel ex vivo patient-derived 3D model of glioblastoma. (12th October 2019) - Brown, Jo; Zaben, Malik; Siebzehnrubl, Florian; P Gray, William
Abstract: There are limited chemotherapeutic options for glioblastoma, which contributes to its poor prognosis. Established cell lines have many phenotypic differences from their original tumours, and drugs showing success in animal models often fail to translate to humans. HiSpots® aim to provide a representative 3D in vitro model of glioblastoma using ex vivo human tumour samples, suitable for mechanistic studies. HiSpots® are a high-density 3D cell culture technique. Cancer and microenvironment cells are mechanically and enzymatically isolated from fresh resected or biopsied tumours, seeded onto PTFE membranes and cultured on an air-liquid interface. Cultures were stained for beta-III tubulin (TUJ1), glial fibrillary acidic protein (GFAP), nestin, and ionized calcium binding adapter molecule 1 (IBA1) to identify tumour cells and microglia. Serum-containing and serum-free media were compared. HiSpots® were created at three densities: low, medium and high, for comparison. Medium density HiSpots® best supported TUJ1+GFAP+Nestin+ tumour cells, and the density did not affect the proportion of microglia. Medium and high density HiSpots® formed multiple cell layers, creating structures up to 40μm thick with variable cell type distribution. Medium and high density HiSpots® and tumour cells were best supported in serum-free media. Medium density HiSpots® cultured in serum-free media have been demonstrated as the best choice to support the heterogeneity of glioblastoma. These HiSpots® contain mostly tumour cells and microglia. HiSpots® therefore allow for the culture of human glioblastoma cells, including microenvironmental microglia. These HiSpot® models will be evaluated as a model for mechanistic studies in the future.